Lectura fonológica en el desarrollo de la comunicación oral en los educandos de sexto año de educación básica de la Escuela Zoila Ugarte de Landívar del cantón Baba, Provincia Los Ríos - Aguilar Buenaño, Carlos Alberto (2019)
The present final report provides significant elements in phonological reading in the development of oral communication in sixth-year students of Basic Education of the School "Zoila Ugarte de Landivar" Baba Canton, Los Rios Province, found flaws in the student learning, because they have not developed the language skills that allow several activities to be done correctly, teachers lack methodological strategies that favor the development of thinking, skills, skills of school children, so they can get involved in society and in the daily life of each person. This research presents within the context the general objectives that are titled below: To promote the practice of phonological reading through expressive activities that lead to the development of an adequate oral communication with the intention of improving its lexicon in future dialogues; addressed during the whole process, in the same way the general problem was raised with the purpose of providing alternative solutions, where existing information related to the topic was collected with contributions and source of ideas to plan, develop the proposal and favor the learning of the students.